Localization of The Global Norm and Efforts to Minimize the Natural Resource Curse in Bojonegoro - Sholikin, Ahmad (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this research is to discuss the efforts of the Bojonegoro Regency Government in translating global norms into local regulations and practices as a measure to minimize the curse of natural resources in Bojonegoro. In general, the state is the main actor in controlling access to natural resources and often maintains the principle of sovereignty in the processes and outcomes of natural resource governance. However, efforts to institutionalize global governance norms at national and sub-national scales often face significant challenges when such global norms come into tension with existing normative frameworks at the local level. Therefore, the Regent of Bojonegoro, Suyoto, initiated the Draft Oil and Gas Petroleum Fund as an effort to minimize the curse of natural resources, which can be seen from several stages of Global Norm Leadership and implementation in Bojonegoro, Opportunities for Bojonegoro Oil and Gas Petroleum Fund Policy Innovation, and Global Norm Localization Initiatives in the Bojonegoro Oil and Gas Petroleum Fund Draft. This research uses quantitative methods. Most of them do regression analysis using panel data or cross-sectional data.